Induced seismicity risk analysis of the hydraulic stimulation of a geothermal well on Geldinganes, Iceland - Broccardo, Marco; Mignan, Arnaud; Grigoli, Francesco; id_orcid:0 000-0002-2858-9756; Karvounis, Dimitrios; Rinaldi, Antonio Pio; id_orcid:0 000-0001-7052-8618; Danciu, Laurentiu; id_orcid:0 000-0003-4086-8755; Hofmann, Hannes; Milkereit, Claus; Dahm, Torsten; et al. (Copernicus, 2020)
The rapid increase in energy demand in the city of Reykjavik has posed the need for an additional supply of deep geothermal energy. The deep-hydraulic (re-)stimulation of well RV-43 on the peninsula of Geldinganes (north of Reykjavik) is an essential component of the plan implemented by Reykjavik Energy to meet this energy target. Hydraulic stimulation is often associated with fluid-induced seismicity, most of which is not felt on the surface but which, in rare cases, can be a nuisance to the population and even damage the nearby building stock. This study presents a first-of-its-kind pre-drilling probabilistic induced seismic hazard and risk analysis for the site of interest. Specifically, we provide probabilistic estimates of peak ground acceleration, European microseismicity intensity, probability of light damage (damage risk), and individual risk. The results of the risk assessment indicate that the individual risk within a radius of 2 km around the injection point is below 0.1 micromorts, and damage risk is below 10−2, for the total duration of the project. However, these results are affected by several orders of magnitude of variability due to the deep uncertainties present at all levels of the analysis, indicating a critical need in updating this risk assessment with in situ data collected during the stimulation. Therefore, it is important to stress that this a priori study represents a baseline model and starting point to be updated and refined after the start of the project. ISSN:1561-8633 ISSN:1684-9981